Biodiversitas Tumbuhan Obat oleh Masyarakat Gampong Pulo Seunong Kecamatan Tangse Kabupaten Pidie - Vera Viena; Irda Yunita; Irhamni Irhamni; Saudah Saudah; Ernilasari Ernilasari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Biodiversity of medicinal plants has been utilized traditionally by the people of Pidie District. This is supported by the level of public awareness will return to nature (back to nature) so as to increase knowledge about medicinal plants. This study aims to identify species of medicinal plants as drugs and parts that are used as medicine. The method used is Direct Observation and Participatory Rural Appraisal through interview with the healer (physician) and the community of drug users. The results showed there were 79 species of medicinal plants from 40 families used as traditional medicine by the community Gampong Pulo Seunong Tangse District Pidie.